Mumbai Metro Line-3: Initial Drive of Tunneling Activities in Package 04 - Ojas Vora; Avinash More; Thinakaran, E. (Asian Journal of Engineering and Applied Technology, 2018)
Mumbai Metro Line -3, indicated as the Colaba-Bandra-Seepz line, is a part of the metro system of the city and is the first underground covering, 33.50km metro line in Mumbai, India. The study area of the tunnel line is between Naya Nagar tunnellaunching shaft and Siddhivinayak Metro station, which is part of Package 04. The distance between these two locations is about 3.6km. The description about the initial drive of tunneling activities, which involves Installation of Piles, Anchoring, lowering of TBM(Tunnel Boring Machine), Mining, Shoving, Mucking, Ring Building and Grouting has been detailed in accordance with the site condition. From the environmental point of view, the problems such as deforestation and flooding have been discussed along with the remedial action.